The Politics of Digital Legal Information Governance: Glocalization of the Legal Documentation and Information Network - Luluardi, Yunas; Lisa Wati , Ayu (AL-QISTHAS: JURNAL HUKUM DAN POLITIK, 2025)
Citizens' rights to obtain information on statutory and regulatory products have not been fully fulfilled. The Legal Documentation and Information Network System (JDIH) continues to develop along with advances in information technology in Indonesia. Because the global world is changing very quickly, society now has access to modern technology, the government is required to provide quality, fast, accurate and objective services. UIN Gus Dur as a new university is making innovations in legal services. The aim of this research is to analyze legal services at JDIH UIN Gus Dur. The method used is qualitative research with a descriptive approach. Data was collected through in-depth interviews with department heads, staff, teaching staff and education staff. then complemented by secondary data collection. The research results show that JDIH UIN Gus Dur has built the JDIH website with the aim of distributing all legal products at the University. Not yet able to take advantage of advances in online technology, but they still cannot access the JDIH Website.